Pengelolaan Kelas dalam Pembelajaran Pendidikan Agama Islam di SDIT Binaul Fikri Serang Baru, Bekasi - Setyaningsih, Faras Afifah; Karyawati, Lilis; Karnia, Nia (FONDATIA, 2023)
Education is the center of teaching and learning activities in the classroom. To achieve the success of educational goals, a professional teacher is needed, one of the criteria for a professional teacher is to be able to manage the class properly and effectively. PAI teachers especially those who teach in the religious field, to achieve the goals of Islamic education, PAI teachers need to pay attention to class management. The purpose of this study is to describe the form of approach and fostering class discipline as well as the constraints and solutions carried out by educators in managing classes in Islamic Religious Education learning at SDIT Binaul Fikri Serang Baru, Bekasi. The research method used is descriptive qualitative with the type of field research. Data collection techniques used are interviews, observation, and documentation. Data analysis uses the Miles and Huberman models. The results of the research show that; (1) The form of the approach used by Islamic Religious Education teachers is a varied approach, including a socio-emotional approach and a permissive approach; (2) The form of classroom discipline that is applied is the conversion method with cooperative control disciplinary techniques; (3) Obstacles faced by PAI teachers in managing classes come from individual and group problems, but these problems can be overcome by preventive methods such as opening, empathy, conversion, accepting and appreciating students as well as curative ways by imposing sanctions.